How to Escape the Middle Income Trap in Iran? Lessons from Malaysia, Thailand South Korea and China - Seyed Hossein Mirjalili; Hossein Saadat (International Economic Studies, 2020)
In 2010, the World Bank categorized countries by GDP (at Purchasing Power Parity) per capita (at constant 1990 prices) in three categories: low, middle (low and high), and high. If a country falls in a trap at least 28 years in the low middle income and at least 14 years in the high middle income group, then it is included in low and middle income groups, respectively. In this paper, using the experience of successful countries in avoiding the trap, we investigated the impact of investment, human capital, high-tech exports, total factor productivity, exports of goods and services, and the value added of service sectors on per capita GDP growth during 1991-2014, using panel data. Research findings in the literature indicated that in selected Asian countries, human capital and total factor productivity growth with positive and significant effects have the greatest impact on avoiding the trap. In the case of Iran, human capital and the total factor productivity growth have positive and significant effects on the economic growth, but such effects have not been so great to help escaping Iran's economy from the middle- income trap. Therefore, Iran has remained in the middle- income trap over the past 58 years.
Keywords: J24; D24; E22; C33; 330; Middle Income Trap; Economic Growth; Human Capital; Education; Productivity